Bacteriophage‐associated genes responsible for the widely divergent phenotypes of variants ofBurkholderia pseudomalleistrain MSHR5848. Issue 2 (February 2019) - DeShazer, David; Lovett, Sean; Richardson, Joshua; Koroleva, Galina; Kuehl, Kathleen; Amemiya, Kei; Sun, Mei; Worsham, Patricia; Welkos, Susan
Abstract : Purpose. : Burkholderia pseudomallei, the tier 1 agent of melioidosis, is a saprophytic microbe that causes endemic infections in tropical regions such as South‐East Asia and Northern Australia. It is globally distributed, challenging to diagnose and treat, infectious by several routes including inhalation, and has potential for adversarial use. B. pseudomallei strain MSHR5848 produces two colony variants, smooth (S) and rough (R), which exhibit a divergent range of morphological, biochemical and metabolic phenotypes, and differ in macrophage and animal infectivity. We aimed to characterize two major phenotypic differences, analyse gene expression and study the regulatory basis of the variation. Methodology. : Phenotypic expression was characterized by DNA and RNA sequencing, microscopy, and differential bacteriology. Regulatory genes were identified by cloning and bioinformatics. Results/Key findings. : Whereas S produced larger quantities of extracellular DNA, R was upregulated in the production of a unique chromosome 1‐encoded Siphoviridae ‐like bacteriophage, ϕMSHR5848. Exploratory transcriptional analyses revealed significant differences in variant expression of genes encoding siderophores, pili assembly, type VI secretion system cluster 4 (T6SS‐4) proteins, several exopolysaccharides and secondary metabolites. A single 3 base duplication in S was the only difference that separated the variants genetically. It occurred upstream of a cluster of bacteriophage‐associated genes on chromosome 2 that were upregulated in S. The first two genes were involved in regulating expression of the multiple phenotypes distinguishing S and R. Conclusion. : Bacteriophage‐associated proteins have a major role in the phenotypic expression of MSHR5848. The goals are to determine the regulatory basis of this phenotypic variation and its role in pathogenesis and environmental persistence of B. pseudomallei .